2021
DOI: 10.3390/genes12071007
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Analysis of Pathogenesis-Related Protein-1 (PR-1) Genes from Piper nigrum Reveals Its Critical Role during Phytophthora capsici Infection

Abstract: Black pepper (Piper nigrum L.) is a prominent spice that is an indispensable ingredient in cuisine and traditional medicine. Phytophthora capsici, the causative agent of footrot disease, causes a drastic constraint in P. nigrum cultivation and productivity. To counterattack various biotic and abiotic stresses, plants employ a broad array of mechanisms that includes the accumulation of pathogenesis-related (PR) proteins. Through a genome-wide survey, eleven PR-1 genes that belong to a CAP superfamily protein wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 62 publications
(81 reference statements)
1
20
0
Order By: Relevance
“…Previous studies on Triticum aestivum and Vitis showed that all PR-1 proteins contain an SP at the N terminal, which could secrete PR-1 proteins into the extracellular environment [14,24]. Two PnPR-1 proteins without SPs were also found in Piper nigrum, which is consistent with the present results [13]. Most CsPR-1 proteins containing an SP at the N terminal might be guided into special subcellular organelles for their biological functions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies on Triticum aestivum and Vitis showed that all PR-1 proteins contain an SP at the N terminal, which could secrete PR-1 proteins into the extracellular environment [14,24]. Two PnPR-1 proteins without SPs were also found in Piper nigrum, which is consistent with the present results [13]. Most CsPR-1 proteins containing an SP at the N terminal might be guided into special subcellular organelles for their biological functions.…”
Section: Discussionsupporting
confidence: 91%
“…PR-1 proteins occur in multigene families within plant genomes and can be further classified as acidic or basic, depending on their theoretical isoelectric point (pI) [12]. Numerous studies have demonstrated that PR-1 proteins abundantly accumulate during plant-defense responses and are ubiquitous across plant species [8,13]. In grapevine ('BN5-4'), the basic-type VvPR1b1 gene confers high resistance against Pseudomonas syringae [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first member of PR-1 family, PR1-a was identified in Nicotiana tabacum plants infected with Tobacco Mosaic Virus (TMV) [4]. Subsequently, several other PR-1 proteins have been identified and characterized in monocot and dicot plant species, such as tomato (Solanum lycopersicum) [5], Triticum aestivum [6], Piper nigrum [7], Grapevine [8], Arabidopsis thaliana, Oryza sativa [9] and cassava (Manihot esculenta) [10]. Their important roles were reported in response to stress conditions [5]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…We have examined miRNA-mediated gene regulation in P. nigrum [ 35 ], tRNA-derived sRNAs effects on the transcriptome of pathogen-infected plants [ 36 ] and the role of microRNA mediated post-transcriptional regulation during P. capsici infections. Moreover, our studies in black pepper during P. capsici infection demonstrated the differential regulation and the presence of phytohormone-responsive transcription activators in the promoter regions of PR-1 genes, which are crucial for SAR induction during pathogen attack [ 37 ]. In our current study, we employ flow-infusion electrospray-high-resolution mass spectrometry (FIE-HRMS) to provide a comprehensive description of the metabolome during quick wilt disease development, both at the site of infection and systemically.…”
Section: Introductionmentioning
confidence: 99%